Role of surface structure in photoelectron emission from solid Ne: impurities, defect and low-coordinated sites - Dmitriev, Yu.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Electron emission was obtained from a solid Ne sample growing from the gas phase on a low temperature substrate. The surface of the sample was irradiated by the light of an open-source microwave discharge running in the gaseous Ne. The irradiation produces electron emission from the sample. A second gas flow of D2 was, simultaneously, passed onto the substrate avoiding the discharge zone. Free electrons ejected into a vacuum chamber during the sample growth were detected by means of the electron cyclotron resonance technique. The emission shows nonmonotonic dependence on the impurity D2 concentration. At small concentration, the electron yield is found to increase significantly at increasing the dopant flow rate, while, at moderate concentrations, the yield tends to decrease with increasing the flow rate. A tentative explanation of the observed effect is presented based on the exceptional properties which the neon-hydrogen solid mixture is believed to have.